2021
DOI: 10.3389/fnins.2021.648863
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Visual Neuroadaptations After Multifocal and Monofocal Intraocular Lens Implantation

Abstract: Visual neuroadaptation is believed to play an important role in determining the final visual outcomes following intraocular lens (IOL) implantation. To investigate visual neuroadaptation in patients with age-related cataracts (ARCs) after phacoemulsification with multifocal and monofocal IOL implantation, we conducted a prospective, controlled clinical trial in Zhongshan Ophthalmology Center. This study included 22 patients with bilateral ARCs: 11 patients underwent phacoemulsification and multifocal IOL (Mu-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
0
10
0
2
Order By: Relevance
“…Contrast sensitivity AUCs showed a remarkable advance in the far range (p = 0.0027), which consequently resulted in the growth of the total AUC (p = 0.0060). We suspect that, similarly to the conventional visual acuity results we had, these early changes after surgery are connected to the anatomical changes in the ocular inner geometry and neuroadaptation processes [31,32], although further investigations need to clarify the exact mechanisms behind.…”
Section: Refractive Aberrations and Notable Angles (Kappa And Alpha)mentioning
confidence: 59%
See 1 more Smart Citation
“…Contrast sensitivity AUCs showed a remarkable advance in the far range (p = 0.0027), which consequently resulted in the growth of the total AUC (p = 0.0060). We suspect that, similarly to the conventional visual acuity results we had, these early changes after surgery are connected to the anatomical changes in the ocular inner geometry and neuroadaptation processes [31,32], although further investigations need to clarify the exact mechanisms behind.…”
Section: Refractive Aberrations and Notable Angles (Kappa And Alpha)mentioning
confidence: 59%
“…Visual acuities measured 1 and 3 months postoperatively were similar, although a slight improvement of distance vision could be observed. This might be due to the modification of the ocular inner geometry after IOL implantation [31], neuroadaptation processes [32], or a slight decentration of the IOL, which was previously reported on the Liberty 677MY lens [17]. An important limitation of our current study is that exact measurements of IOL decentration were not performed, and therefore, its contribution to visual outcomes could not be assessed.…”
Section: Refractive Aberrations and Notable Angles (Kappa And Alpha)mentioning
confidence: 82%
“…However, we found no correlation between quality of vision scores and follow-up time; recent research has suggested that neuroadaptation occurs within 3 months of implantation of either a monofocal or multifocal IOL. 24 In conclusion, the Vivity IOL provided patients with good distance and intermediate vision, and functional near vision; with most subjects reporting little or no bother from glare, halos, or starbursts.…”
mentioning
confidence: 77%
“…In addition, in PACG patients, the left cuneus had significant lower fALFF values, but the data of this study showed that the change direction of average fALFF value of the left anterior cuneus was as the same as the trend of the patients' MDVF and RNFL thickness changes ( 42 ). In a half-year study on the adaptation of the optic nerve after cataract intraocular lens implantation, it was found that the increased fALFF value represented the brain's activation of the optic nerve adaptation mechanism: the decreased fALFF value suggested the adaptability of patient's visual function is inhibited, and the fALFF value of patients in the same group could changes from low to high or from high to low at different stages of visual function adaptation ( 59 ). Our current study found that in OH patients, the average fALFF value of the LP area was higher than that of the Hc group, which is the same as the conclusion drawn by the study of RP ( 36 ) and NVG ( 43 ).…”
Section: Discussionmentioning
confidence: 99%